Sexual harassment in the workplace - Joni Hersch (IZA World of Labor, 2015)
Workplace sexual harassment is internationally condemned as sex discrimination and a violation of human rights, and more than 75 countries have enacted legislation prohibiting it. Sexual harassment in the workplace increases absenteeism and turnover and lowers workplace productivity and job satisfaction. Yet it remains pervasive and underreported, and neither legislation nor market incentives have been able to eliminate it. Strong workplace policies prohibiting sexual harassment, workplace training, and a complaints process that protects workers from retaliation seem to offer the most promise in reducing sexual harassment.
Keywords: J16; J71; J81; J83; K31; K42; 330; sexual harassment; sex discrimination; workplace violence; productivity; earnings